Information-Seeking Behaviour Model of International Students’ Use of Social Media - Bukhari, Sarah; Hamid, Suraya; Ravana, Sri Devi; Ijab, Mohamad Taha (2018)
The purpose of this paper is to propose a model of information-seeking behaviour (ISB) of international students when they are using social media.A netnography is conducted on Facebook and we evaluated the both posts/comments. A thematic coding was performed on the both posts/comments and we have identified two main themes as information needs and information source, which were divided into sub-themes. Information needs are the information that international students required in a new environment. On the other hand, information source provides the solutions to fulfil the information needs. With the help of netnography and extant literature, this paper proposes the model of ISB of international students’ use of social media. This study enhances the previous models of ISB and offers future research direction in validating the new model.